Differential mutation frequencies in metastatic cutaneous squamous cell carcinomas versus primary tumors - Yilmaz, Ayse Selen (Cancer, 2016)
BACKGROUND: Exome and targeted sequencing studies have identified potential driver mutations for a variety of tumor types. Cutaneous squamous cell carcinoma (cSCC) is one of the most highly mutated cancers but is typically associated with low rates of metastasis and high survival rates. Nevertheless, metastatic cSCC is a significant health threat; up to 8800 individuals die yearly from this disease. METHODS: As it is difficult to predict which cSCCs are more likely to metastasize, and because there are no targeted therapies specifically designated for metastatic cSCC, we performed exome and/or targeted sequencing of 18 metastatic and 10 primary cSCCs to identify mutations that were more frequent in metastatic tumors and might be targeted for therapeutic benefit. We compared our results to published sequencing results of an additional 223 primary tumors and 68 metastatic cSCCs. RESULTS: We identified genes showing higher mutation frequencies in metastatic cSCC relative to primary tumors including the chromatin remodeling gene KMT2D and the classic skin tumor suppressor TP53 which was mutated in 54% of primary tumors relative to 85% of metastatic tumors (p <0.0001). CONCLUSIONS: These studies uncover potential pathways important in metastatic cSCC that broaden our understanding of the biology contributing to aggressive tumor behavior and may lead to new therapeutic strategies.